Performance of improved water management technology on rice grown in the Chambal command area of South-Eastern Rajasthan - Narolia, R. S.; Verma, A. K.; Singh, Pratap (Annals of Agricultural Research, 2018)
On farm demonstrations were conducted during kharif seasons of 2011 to 2015 at farmer's field inChambal command area of Rajasthan under Operational Research Programme of AgriculturalResearch Station, Kota to study the impact of improved water management technology on the waterproductivity and sustainability of rice. Treatments comprised irrigation of 5Â±2 cm standing waterand refilling at 1-3 days after disappearance of ponded water which was compared with the farmerspractice (FP) i.e. continuous submergence. Results revealed that improved water managementtechnology gave higher and sustainable yield of rice over the years. The mean grain yield (4,506kg/ha), production efficiency (34.7 kg/ha/day) and crop monetary efficiency (` 884/ha/day)recorded under IWMT being 7.5, 7.8 and 8.33 per cent higher as compared to the farmers practice,respectively. Mean sustainability yield index (0.932) and sustainability value index (0.913) werefound 4.04 and 5.18 percent higher under IWMT in comparison to FP, respectively. Mean waterexpanse efficiency (89.0 kg/ha-cm), water use efficiency (36.7 kg/ha-cm), water profitability (9.45`/M3) and incremental cost benefit ratio (6.4) observed were also better in IWMP than farmerspractice.